Bovine Genome-Microbiome Interactions: Metagenomic Frontier for the Selection of Efficient Productivity in Cattle Systems - Phillip R. Myer (American Society for Microbiology, 2019)
ABSTRACT The mutualistic, commensal, and parasitic microorganisms that reside in the rumen and lower gastrointestinal tract of cattle and other ruminants exert enormous influence over animal physiology and performance. Because these microbial communities are critical for host nutrient utilization and contribute to the metabolic capacity of the rumen, past research has aimed to define host-microbe symbioses in cattle by examining the rumen and lower gut microbiomes with respect to production phenotypes, such as feed efficiency. However, as the field of bovine gut microbial ecology progresses, multidisciplinary approaches must be employed, combining host genomics and other omics-based techniques to understand the complex host-microbe network. In this perspective, I discuss the direction of the field of bovine gut microbial ecology with regard to feed efficiency and explore how the grand challenge of such research will be to maintain host-efficient gut microbiomes in cattle production through manipulations of genome-microbiome interactions.